Does political instability lead to higher inflation? A panel data analysis - Veiga, Francisco José (2005)
Economists generally accept the proposition that high inflation rates generate inefficiencies that reduce society’s welfare and economic growth. However, determining the causes of the worldwide diversity of inflationary experiences is an important challenge not yet satisfactorily confronted by the profession. Based on a dataset covering around 100 countries for the period 1960-1999 and using modern panel data econometric techniques to control for endogeneity, this paper shows that a higher degree of political instability is associated with higher inflation. The paper also draws relevant policy implications for the optimal design of inflation stabilization programs and of the institutions favorable to price stability.